1999
DOI: 10.1212/wnl.52.3.646
|View full text |Cite
|
Sign up to set email alerts
|

Hemiballismus–hemichorea in older diabetic women: A clinical syndrome with MRI correlation

Abstract: Eight older women from two different continents, all with nonketotic hyperglycemia, presented with hemiballismus-hemichorea (HB-HC) and high signal intensity in the contralateral striatum on T1-weighted MRI scans. Correction of underlying hyperglycemia and supportive care resulted in resolution within days to weeks. This characteristic clinicoradiologic picture suggests a clinical syndrome with benign outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
2
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 4 publications
7
59
2
6
Order By: Relevance
“…Os autores especulam sobre a hipersensibilidade à dopamina em mulheres no período pós-menopausa, conforme já descrito no estudo de Lin e Chang 7 . Os autores enfatizam ainda a correta definição desta síndrome em face das aplicações terapêuticas, pois a correção da hiperglicemia, com a utilização temporária de haloperidol e/ou diazepam, levarão a rápida melhora do quadro de hemibalismo-hemicoréia 11 .…”
Section: Discussionunclassified
“…Os autores especulam sobre a hipersensibilidade à dopamina em mulheres no período pós-menopausa, conforme já descrito no estudo de Lin e Chang 7 . Os autores enfatizam ainda a correta definição desta síndrome em face das aplicações terapêuticas, pois a correção da hiperglicemia, com a utilização temporária de haloperidol e/ou diazepam, levarão a rápida melhora do quadro de hemibalismo-hemicoréia 11 .…”
Section: Discussionunclassified
“…Anterior parietal arter inmesi sonrası; santral ağrı ile birlikte eş zamanlı hemiballismus tarif edilmiştir (18). Manyetik Rezonans Görüntüleme (MRG) çalışmalarında; kontralateral striatumun yüksek sinyal intensitesi gösterdiği, ketotik olmayan hiperglisemi hastalarında da hemiballismus ve hemikore tarif edilmiştir (19). Hemiballismusa sıklıkla subtalamusun hemorajik veya iskemik lezyonları yol açar (20).…”
Section: Hemiballismus;unclassified
“…In two of them, the hyperkinesia was the initial presenting symptom of diabetes. Soon after this description, Lee et al 52 reported on eight female diabetic patients with HB-HC, further characterizing the clinical syndrome with magnetic resonance imaging (MRI) correlation (contralateral high signal intensity putaminal lesion without edema or swelling on T1-weighted MRI). Finally, Mestre et al 53 presented the pathological correlate of the imaging findings, defining that putaminal petechial haemorrhages in a fatal case of nonketotic hyperglycemia chorea.…”
Section: Acute Chorea and Hemiballismhemichoreamentioning
confidence: 99%
“…Mild chorea often does not require treatment; however, when the hyperkinetic movements are of sufficient severity to cause functional disability and exhaustion, several different approaches have been advocated 47,[50][51][52][53][54] . A combination of a benzodiazepine with either haloperidol, olanzapine or tetrabenazine, titrated over days to maintain a balance between control of the movement disorder and side effects, such as sedation, can be effective 47,50,51 .…”
Section: Acute Chorea and Hemiballismhemichoreamentioning
confidence: 99%